Isolation And Identification Of Biosurfactant Producing Bacteria In Sediments From The Coastal Area Of Mengkapan Village, Sungai Apit Distict, Siak Regency, Province Of Riau - Kristina M, Martha Novia; M. Hasbi, M. Hasbi; Purwanto, Eko (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTThe activities of petroleum drilling, ferry ports and leakages of underwater pipeline caused oil pollution in the coastal area of the Mengkapan Village.The oil pollutant will be carried by the waves and settles to the sediment and it may causing genetic changing in the microorganisms present in the sediment. The presence of oil pollution may trigger gene mutation in specific bacteria and it may be able to produce biosurfactants for degrading the oil. A study aims to investigate of biosurfactant producing bacteria in the sediment of the coastal area of Mengkapan Village was conducted from March to May 2018. There were 2 stations, in the petroleum drilling area (St1) and in the Tanjung Buton port (St2). Morphological and biochemical characeristics shown that there were 3 bacteria species, namely Bacillus sp, Proteus sp and Pseudomonas sp present. Emulsification Index of the Bacillus sp was 42,85%, the Pseudomonas sp was 53%,and Proteus sp was 25%, indicating that all bacteria obtained were potencial for producing biosurfactant. Keyword : Oil pollutant ,Pseudomonas sp , Emulsification Index, Biodegradation